Perjuangan Lembaga Swadaya Masyarakat Koalisi Perempuan Indonesia Kota Semarang dalam Membela Hak-Hak Buruh Perempuan di Kota Semarang - Utami, Luwes Tri; Lestari, Puji; Handoyo, Eko (Unnes Political Science Journal, 2017)
The role of women in the increase in activity of income, has lasted for so long. Along with the rapid progress industry in cities have pushed female workers into the sector. This leads to the increasing the number of job seekers female who did not accompanied by job are available so that allegedly they have to accept payment system and social security and occupational safety by the company, though often reflect treatment discriminatory and exploitation in various companies/industry. This study attempts to analyze perjuanganan obstacles ngos coalition women in indonesia semarang city in defending hak-hak workers women in semarang city. This research result indicates that struggle ngos coalition women in indonesia semarang city in defending hak-hak workers women in semarang city done through politics is included in the wages council and advocacy or penjembatan cases rights workers .Through the field non political done by providing information or training for workers in the form of education in class .In addition , the obstacles coalition women in indonesia semarang city covering internal problems of the time , and constraint ekstern derived from workers fear of workers , time , and thought pragmatic .Advice provided is increase it members and the performance of interest groups workers.